A statistical study of energetic particle events associated with interplanetary shocks observed by Solar Orbiter in solar cycle 25 - Kartavykh, Y.; Rodriguez-Garcia, L.; Heber, B.; Wimmer-Schweingruber, R. F.; Trotta, D.; Gieseler, J.; Droege, H.; Kollhoff, A.; Droege, W.; Kilpua, E.; Horbury, T.; Espinosa Lara, F.; et al. (EDP Sciences, 2025)
Context. We studied energetic particle intensity profiles observed by Solar Orbiter during the time period from April 2020 to April 2023, associated with the passage of interplanetary (IP) shocks. For our study we considered 58 IP forward shocks and analysed the possible correlations between some IP shock parameters and the electron and proton responses to the passage of the IP shocks. We investigated which shock signatures are more likely related to the efficiency of the IP shocks with respect to particle acceleration.
Aims. We introduced a variable that characterises the contamination induced by protons in the electron channels of the Electron Proton Telescope (EPT) part of the Energetic Particle Detector (EPD) suite of instruments on board Solar Orbiter, which allowed us to identify the cases in which the intensity time profiles of electrons at energies <= 240 keV showed a real response at the passage of IP shocks. In the case of protons, we searched for the response in seven energy ranges from 52 keV to 15 MeV, and based on the shape of the proton response at low energies (similar to 100 keV), we divided the profiles into weak responses, peaks (regular or irregular), plateaus, and unclear responses. For the regular peak and plateau types we constructed an average time profile by applying superposed epoch analysis. For the response in electrons and protons, and for the different types of proton responses at different energies, we analysed the corresponding IP shock parameters, aiming to understand which ones are important to form a certain type of time profile or to achieve a certain energy. We also included a comparison between the proton intensity time profiles in the upstream region and, assuming the predictions of the diffusive shock acceleration (DSA) theory, identified the values of the mean free path in several cases.
Methods. We found that the IP shock efficiency in the energisation of both electrons and protons is strongly energy dependent. Cases of electron acceleration are rare. Only in about similar to 8% of the events for energies <= 100 keV and in similar to 2% for energies <= 250 keV did the electron intensities show an unambiguous response at the passage of IP shocks (with those accompanied by a response being mainly oblique or quasi-perpendicular). The shocks for which we identified a response in similar to 100 keV proton intensity time profiles come to similar to 83% of the IP shocks under study, and are parallel or quasi-parallel. The ability to accelerate protons to higher energies and to form a particular shape of the particle response to the IP shock passage mostly depends on the IP shock speed.
Results. Based on the analysis of time profiles and the occurrence of unambiguous electron acceleration at shocks, the acceleration mechanism behind the electron energisation is unlikely to be DSA, but shock drift acceleration (SDA) remains a candidate for the acceleration mechanism. Proton time profiles of the plateau type around the IP shock front can be achieved with an IP shock speed above 800 km s(-1) and an ambient mean free path <= 0.015 au, reproducing the asymptotic steady-state ion distribution reached in the classical DSA solution.